Tick Size, Trading Strategies, and Market Quality - Werner, Ingrid M.; Rindi, Barbara; Buti, Sabrina; Wen, Yuanji (Management Science, 2023)
We investigate the effects of a tick-size reduction on market quality in a multiperiod limit order book market. For illiquid stocks, reducing the tick size facilitates undercutting and discourages liquidity provision, resulting in deteriorating market quality but higher volume. For liquid stocks, reducing the tick size curtails queues, resulting in lower depth and volume but narrower spread. With a competing crossing network, a tick-size reduction results in worse market quality for all stocks due to migration of order flows. We empirically test our model predictions and find support for recent tick-size reductions in Japan and the United States. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The data files and online appendices are available at https://doi.org/10.1287/mnsc.2022.4502 .